Changes in liver fibrosis in HIV/HCV‐coinfected patients following different outcomes with peginterferon plus ribavirin therapy. Issue 7 (6th October 2013) - Labarga, P.; Fernandez‐Montero, J. V.; Barreiro, P.; Pinilla, J.; Vispo, E.; de Mendoza, C.; Plaza, Z.; Soriano, V.
Summary There is scarce information about the impact of antiviral treatment on subsequent progression of liver fibrosis in HIV‐infected patients with chronic hepatitis C who experience different outcomes following peginterferon‐ribavirin therapy. We conducted a retrospective study of a cohort of HIV/HCV‐coinfected patients with longitudinal assessment of liver fibrosis using elastometry. Patients were split out into four groups according to the prior peginterferon‐ribavirin response: sustained virological response (SVR), relapse (R), partial response (PR) and null response (NR). A group of untreated, coinfected patients was taken as control. Significant liver fibrosis progression (sLFP) was defined as a shift from baseline Metavir estimates ≤F2 to F3‐F4, or by >30% increase in liver stiffness in patients with baseline F3‐F4. Conversely, significant liver fibrosis regression (sLFR) was defined as a shift from baseline Metavir estimates F3‐F4 to ≤F2, or by >30% reduction in liver stiffness in patients that kept on F3‐F4. A total of 498 HIV/HCV‐coinfected patients were examined. They were classified as follows: 138 (27.7%) SVR, 40 (8%) R, 61 (12.2%) PR, 71 (14.3%) NR and 188 (37.8%) naive. After a mean follow‐up of 53.3 months, sLFP occurred less frequently in patients with SVR (7.2%) compared with R (25%; P = 0.002), PR (23%; P = 0.002), NR (29.6%; P < 0.001) and naïve (19.7%; P = 0.002). Conversely, sLFR was 26.1% in SVR compared with 10% in R (P = 0.03), 14.8% in PR (P = 0.06), 16.9% in NR (P = 0.07) and 10.6% in naïve (P < 0.001). Sustained clearance of serum HCV‐RNA following a course of antiviral treatment is the major determinant of liver fibrosis regression in HIV/HCV‐coinfected patients.